1966
DOI: 10.1002/cpt196674510
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of adrenergic neuron blockade in hypertensive subjects

Abstract: The effects of dextroamphetamine, methamphetamine, methylphenidate, nialamide, imipramine, and ephedrine

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

1967
1967
1997
1997

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 3 publications
3
6
0
Order By: Relevance
“…This observation would be consistent with two studies that failed to show guanethidine antagonism following a single dose of TCA (100,101).…”
Section: Drug Interactions With Tricyclic Antidepressantssupporting
confidence: 85%
“…This observation would be consistent with two studies that failed to show guanethidine antagonism following a single dose of TCA (100,101).…”
Section: Drug Interactions With Tricyclic Antidepressantssupporting
confidence: 85%
“…Clinical observations also indicate that amphetamine and related drugs specifically antagonize the hypotensive action of bretylium and guanethidine (Gulati, Dave, Gokhale & Shah, 1966). In the present experiments methylamphetamine could reverse the block by xylocholine, bretylium or guanethidine of the responses to stimulation of the postganglionic sympathetic nerve.…”
Section: Discussionsupporting
confidence: 51%
“…For example, it has been reported that s-adrenergic blocking agents can protect a-adrenergic receptors against POB blockade (Olivares et ~., 1967;Patil et ~., 1968), and this effect has been attributed to a competition between a-and s-adrenergic blocking agents for receptor sites (Gulati et ~., 1965). The finding that hypothermia (15 0 C) abolished s-adrenergic reactivity of the cardiovascular system in the dog and rat, while a-adrenergic reactivity was maintained, is also consistent with the above concept (Price et~., 1967).…”
Section: \mentioning
confidence: 99%